2020
DOI: 10.3389/fnagi.2020.00021
|View full text |Cite
|
Sign up to set email alerts
|

Laterality of Attentional Networks in Patients With Cerebral Small Vessel Disease

Abstract: Introduction: Problems with attention are common in patients with cerebral small vessel disease (CSVD). The normal human brain exhibits functional and structural asymmetry. However, it is unknown whether there is lateralization of attention in patients with CSVD. Objective: This study aims to investigate attention separately in both cerebral hemispheres in patients with CSVD using the computer-based Lateralized Attention Network Test-Revised (LANT-R). Methods: The total number of subjects included was 58, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…Meanwhile, we discovered that total CSVD score was significantly correlated with attention network efficiencies as measured by the ANT ( Table 5 ), but not with global cognition as measured by the MoCA scores or with executive function as measured by scores on this MoCA subdomain, indicating that higher total CSVD loads would lead to more severe impairments in orienting and executive control, together with providing indirect evidence that the sensitivity of ANT was promising. Likewise, it was verified in our investigation that WMHs grade could affect magnitude and speed of attentional processing ( 13 ), and negative relationship between orienting efficiency of right hemisphere and WMHs lesions was observed for patients with CSVD in another study ( 39 ). Since total CSVD score was related to cognitive decline and incident dementia ( 8 , 29 ), the correlations reported in this study highlighted possible damage of brain regions responsible for attention networks in patients with CSVD and modulation of total lesion burdens; hence, early diagnosis and treatment for CSVD might mitigate brain pathology associated with cognitive deficits.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Meanwhile, we discovered that total CSVD score was significantly correlated with attention network efficiencies as measured by the ANT ( Table 5 ), but not with global cognition as measured by the MoCA scores or with executive function as measured by scores on this MoCA subdomain, indicating that higher total CSVD loads would lead to more severe impairments in orienting and executive control, together with providing indirect evidence that the sensitivity of ANT was promising. Likewise, it was verified in our investigation that WMHs grade could affect magnitude and speed of attentional processing ( 13 ), and negative relationship between orienting efficiency of right hemisphere and WMHs lesions was observed for patients with CSVD in another study ( 39 ). Since total CSVD score was related to cognitive decline and incident dementia ( 8 , 29 ), the correlations reported in this study highlighted possible damage of brain regions responsible for attention networks in patients with CSVD and modulation of total lesion burdens; hence, early diagnosis and treatment for CSVD might mitigate brain pathology associated with cognitive deficits.…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, Pedro et al discovered that patients with MCI with subcortical vascular damage exhibited smaller orienting effect compared with patients free from subcortical vascular damage and controls ( 38 ), and subcortical lesions caused by RSSIs and deep WMHs are prevalent for CSVD. Nevertheless, via a lateralized ANT-revised paradigm, Cao et al reported that orienting efficiency of right hemisphere was higher in CSVD group, which could be explained by adaptive compensation hypothesis ( 39 ). The divergencies might arise from distinct ANT stimuli and individual criteria for participant enrolment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As suggested by prior publication, traditional neuropsychological assessment tools displayed different sensitivities and specificities in screening of cognitive impairment, for instance, MoCA possessed higher sensitivity (0.97 vs 0.65) while lower specificity (0.60 vs 0.89) compared with MMSE. 39 Nevertheless, divergent results have been obtained for neuropsychological evaluation by other CSVD-related reports, 5 , 40 and the inconsistencies might arise from diverse subject selection criteria and research protocols, which needs to be illuminated in future investigation using larger cohorts. Notably, mean amplitudes of sad EMMN were markedly attenuated in CSVD sufferers than those in healthy controls, implying that EMMN component could serve as a reliable biomarker to reflect dysfunction of emotional processing and ERP experiments might detect early cognitive decline sensitively for CSVD, at least indicated by this study.…”
Section: Discussionmentioning
confidence: 99%
“…The neuropsychological scale of the Chinese Cerebral Small Vessel Disease Clinical Evaluation Study was used to evaluate the global cognitive function and individual cognitive functions of all participants ( Cao et al, 2020 ). The Montreal Cognitive Assessment (MoCA) was used to measure global cognitive function ( Nasreddine et al, 2005 ).…”
Section: Methodsmentioning
confidence: 99%